Sustainability Evaluation of Rural Infrastructure Through The Participatory IMAP Approach: A Case Study of Ayula Selatan Village, Gorontalo - Lihawa, Fitryane; Harun, Ervan; Machmud, Achmad Nur Fahry; Mahmud, Marike (Jambura Geoscience Review, 2026)
Rural communities often face persistent challenges in achieving sustainable rural development due to limited technical capacity, low community participation, and weak institutional coordination in managing public infrastructure. This study evaluates the sustainability of community-based infrastructure in Ayula Selatan Village by integrating technical, social, and institutional dimensions within a participatory governance framework. A participatory qualitative approach—combining transect walks, interviews, and IMAP surveys was used to assess the performance of the community-based Drinking Water Supply System (SPAM), Domestic Wastewater Management System (SPAL), and the 3R Waste Management Facility (TPS 3R). Data were collected from 294 households to examine the system’s functionality and community engagement. Findings show that 98% of households rely on bore wells, while only one communal wastewater treatment facility serves 50 households in limited coverage. The village operates a single TPS 3R with insufficient labor and transportation, resulting in inefficient waste processing. Strong links were observed between technical reliability, participatory governance, and sanitation sustainability, where greater community involvement fostered greater ownership, accountability, and long-term infrastructure performance. Institutional partnerships further enhanced operational resilience through collaborative management. Overall, the study highlights that sustainable rural development depends on synergy between technical robustness, social empowerment, and institutional collaboration. Strengthening participatory frameworks and local capacity is essential for improving the management and long-term sustainability of community-based rural infrastructure.